Synthesis, Characterization, and Docking Studies of 1,4-dien as a Potential Impurity in Bimatoprost Drug - Guttikonda, Nagarjuna Reddy; Venkatanarayana, Muvvala; Haridasyam, Sharath Babu (Current Organic Synthesis, 2025)
IntroductionThe origin, synthesis, characterization and docking studies of (Z)-7-((1R,2R,3R,5S)-3,5-dihydroxy-2-((R,1E,4E)-3-hydroxy-5-phenylpenta-1,4-dien-1-yl)cyclopentyl)-N-ethylhept-5-enamide, an impurity generated in the preparation of an anti-glaucoma agent-Bimatoprost has been described.MethodsThis impurity was controlled by employing 30% Pd/C, and the impurity level was brought to the permissible level, i.e., 0.03% (ICH guidelines) in the final drug preparation of Bimatoprost.ResultsFinally, induced-fit docking calculations were performed to theoretically evaluate the binding efficiencies of these inhibitors in the crystal structure of Prostaglandin F synthase (PGFS).ConclusionThere are negligible differences in RMSD and docking scores between the two ligands, which amount to only 0.18 Å and 0.313 kcal/mol, respectively. These findings strongly indicate that both ligands are likely to exhibit similar biological functions and efficiencies.
Keywords: docking studies